2010
DOI: 10.1002/pmic.201000241
|View full text |Cite
|
Sign up to set email alerts
|

Dual energy landscape: The functional state of the β‐barrel outer membrane protein G molds its unfolding energy landscape

Abstract: We applied dynamic single-molecule force spectroscopy to quantify the parameters (free energy of activation and distance of the transition state from the folded state) characterizing the energy barriers in the unfolding energy landscape of the outer membrane protein G (OmpG) from Escherichia coli. The pH-dependent functional switching of OmpG directs the protein along different regions on the unfolding energy landscape. The two functional states of OmpG take the same unfolding pathway during the sequential unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 61 publications
(124 reference statements)
3
12
0
Order By: Relevance
“…The free unfolding energies, ΔG u , ranging between 21 to 28 k B T (Table 1) were similar to those reported in literature (22,33,(36)(37)(38). Most pronounced changes were observed again for EH2 in which the free unfolding energy dropped in the presence of K þ by 3-5 k B T. In contrast, the free unfolding energies of all other structural regions showed much smaller changes, which suggest that they were largely independent of the presence of K þ and betaine.…”
Section: Whereas Insupporting
confidence: 71%
“…The free unfolding energies, ΔG u , ranging between 21 to 28 k B T (Table 1) were similar to those reported in literature (22,33,(36)(37)(38). Most pronounced changes were observed again for EH2 in which the free unfolding energy dropped in the presence of K þ by 3-5 k B T. In contrast, the free unfolding energies of all other structural regions showed much smaller changes, which suggest that they were largely independent of the presence of K þ and betaine.…”
Section: Whereas Insupporting
confidence: 71%
“…This includes the distance x u from the folded state to the transition state towards unfolding, which characterizes the width of the energy valley that stabilizes the folded structure. Our analysis revealed that x u values in hVDAC1 were ~30–50% larger than those determined for α-helices of most transmembrane proteins (Janovjak et al, 2008), and comparison with results for the transmembrane β-barrel of OmpG suggested the same trend (Damaghi et al, 2010). In addition, we obtained quantitative information about the mechanical rigidity of the hVDAC1 channel: its mechanical rigidity is comparable to that of different transmembrane α-helices (Kawamura et al, 2013; Zocher et al, 2012), but is a factor 2–10 below that of the β-strands of the transmembrane β-barrel protein OmpG (Damaghi et al, 2010).…”
Section: Discussionsupporting
confidence: 47%
“…Measuring the kinetic response of the individual structural elements by dynamic SMFS (DFS) allows quantification of their unfolding free energy, kinetic stability, conformational variability, and mechanical flexibility (33). Both SMFS and DFS have been applied to characterize these parameters of various membrane proteins and follow how they change on changing their functional state or physiological environment (34)(35)(36)(37)(38)(39).…”
mentioning
confidence: 99%